Microvascular Anastomotic Coupler Assessment in Head and Neck Reconstruction. Issue 1 (12th April 2013) - Frederick, John W.; Sweeny, Larissa; Carroll, William R.; Rosenthal, Eben L.
Abstract : Objective: To assess the advantages of using mechanical anastomotic systems in head and neck free tissue transfer. Study design: Case series with chart review. Setting: A university‐based tertiary care center. Subjects and Methods: A retrospective review of mechanical venous coupler devices in head and neck reconstruction performed between October 2004 and December 2006. A total of 261 venous anastomoses were performed in 234 consecutive patients. Five types of flaps were performed: radial forearm (66%), anterior lateral thigh (12%), fibula (9%), rectus abdominis (8%), and latissimus dorsi (2%). Demographic data were collected, and the outcomes measured were flap survival and microvascular complications. Results: The size of the venous anastomosis ranged from 1.5 to 4.0 mm, with most being 3.0 mm (56%) followed by 3.5 mm (23%). The most common recipient vein used was a stump off the internal jugular vein (76%) followed by the external jugular vein (17%). Microvascular complications occurred in <5% (n = 11) of patients, with >50% of those being arterial insufficiency (n = 7). Total failures occurred in 3% (n = 7) of patients: 1.5% (n = 4) acute failures (<5 days) and 1.5% (n = 3) late failures. Of the acute failures, causes included venous congestion (n = 1) and arterial insufficiencies (n = 3). The venous coupler used in the failures was 3.0 mm in diameter. Free flap failures resulting from arterial insufficiency involved coupling to the external jugular vein, while the remaining free flap failures (n = 4) used the internal jugular vein. Conclusion: With an early venous failure rate of 0.38%, mechanical anastomosis is an adequate alternative to hand‐sewn techniques.